High strength bioinspired calcium phosphate-based material for bone repair applications. (December 2022) - Mussatto, Andre; Doğu, Merve Nur; Vijayaraghavan, Rajani K.; Groarke, Robert; Obeidi, Muhannad Ahmed; McGuinness, Garrett B.
Abstract: Owing to the increasing demand for bone repair strategies, several biomaterials have been developed. Among the materials available for this purpose, hydroxyapatite stands out for its osteoinduction capacity, since it possesses a chemical composition similar to that of inorganic bone constituents. In comparison to bones, the mechanical properties of substitute structures incorporating hydroxyapatite still remain a great challenge for scientists. This study thus presents the synthesis of hydroxyapatite incorporated with a natural bioceramic and a metallic phase of excellent biocompatibility to obtain dense biomaterials with improved mechanical strength. The mechanical responses of the synthesized biomaterials are presented and discussed. The results obtained indicate that the hydroxyapatite-natural ceramic systems fulfils the general mechanical property requirements for some bone repair applications. Separately, the synthesis of titanium-based systems was shown to be much more challenging, but promising. Therefore, recommendations for suppressing the issues with the metal-ceramic interfacial bonding strength were provided. Graphical Abstract: ga1 Highlights: A simple method of synthesising hydroxyapatite composites for biomedical applications is presented. Titanium-reinforced composites with calcium phosphate content close to natural bone were developed. Waste seashells were used for extraction and recovery of valuable calcium oxide compounds. Hydroxyapatite-based calcium oxide composites with high mechanical performance were synthesised.